Phenotype and function of HBV-specific T cells is determined by the targeted epitope in addition to the stage of infection. Issue 5 (22nd December 2018) - Hoogeveen, Ruben C; Robidoux, Maxwell P; Schwarz, Tatjana; Heydmann, Laura; Cheney, James A; Kvistad, Daniel; Aneja, Jasneet; Melgaço, Juliana G; Fernandes, Carlos A; Chung, Raymond T; Boonstra, Andre; Kim, Arthur Y; et al.
Abstract : Objective: Chronic HBV infection affects more than 250 million people worldwide and remains a global healthcare problem in part because we lack curative treatment. Sustained viral control requires HBV-specific T cells, but these become functionally impaired in chronic infection. Clinical evidence indicates that functional cure of HBV infection by the host immune response is feasible. Developing T cell-based therapies able to achieve functional cure will require identification of the requirements for a successful T cell response against HBV and the relative contribution of individual T cell specificities to HBV control. Design: The phenotype and function of HBV-specific T cells were studied directly ex vivo using fluorochrome-labelled multimers. We studied multiple HBV-specific T cell specificities targeting different HBV proteins in individuals with either an acute self-limiting or chronic HBV infection. Results: We detected strong T cell responses targeting multiple HBV viral proteins in acute self-limiting and low-frequency core and polymerase-specific T cells in chronic infection. Expression of the T cell inhibitory receptor PD-1, as well as T cell differentiation, T cell function and T cell regulation differed by stages and outcomes of infection. In addition, these features differed significantly between T cells targeting different HBV specificities. Conclusion: HBV-specific T cells with different target specificities are characterised by distinct phenotypical and functional profiles. These results have direct implications for the design of immunological studies in HBV infection, and are potentially relevant for informing immunotherapeutic approaches to induce functional cure.